Pengaruh Pengaruh Variasi Tinggi Cover Collector Distilasi Surya Pasif Terhadap Produktivitas Distilat - Daniel Marwill Djoe; Ben V Tarigan; Muhamad Jafri (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
Clean water is a vital resource that is increasingly difficult to obtain in many regions of the world, including Indonesia, which faces significant challenges in providing clean water. Passive solar desalination is an efficient alternative method to convert seawater into fresh water by utilizing solar energy. This study aims to analyze the effect of varying cover collector heights on distillate productivity in passive solar desalination, using charcoal as an energy-absorbing material. The varied cover collector heights used were 30 cm, 45 cm, and 55 cm. The results of the study show that the smaller the distance between the seawater surface and the cover collector, the higher the distillate productivity. Basin 1 (30 cm) produced the highest distillate (120 ml), followed by Basin 2 (45 cm) with 94 ml, and Basin 3 (55 cm) with 60 ml. This indicates that a smaller gap between the cover collector and the seawater surface increases the evaporation and condensation rates, contributing to higher distillate productivity.